2006
DOI: 10.1117/12.659411
|View full text |Cite
|
Sign up to set email alerts
|

High performance TAC film for LCDs

Abstract: Tri-acetyl cellulose (TAC) films are widely used as a protective film for polarizers because it has high light transmittance, low birefringence, high moisture permeability, high uniformity and good curling property. This paper describes TAC film technologies, especially about the birefringence control of TAC film. Making use of the controlled birefringence, the TAC film comes to take an active role in optical compensation of LCDs as well as protection of polarizers. The out-of-plane birefringence of the TAC fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…TAC film is widely used as a protective and supporting film for the PVA layer by virtue of high light transmittance (>93%), low birefringence, high moisture resistance, high thermal-stability, high uniformity and good curling ability [23][24][25][26]. The chemical structure of the TAC is shown in Fig.…”
Section: Polarizer Filmmentioning
confidence: 99%
“…TAC film is widely used as a protective and supporting film for the PVA layer by virtue of high light transmittance (>93%), low birefringence, high moisture resistance, high thermal-stability, high uniformity and good curling ability [23][24][25][26]. The chemical structure of the TAC is shown in Fig.…”
Section: Polarizer Filmmentioning
confidence: 99%
“…Alternatively, solution casting is usually used for the preparation of CTA optical films in industrial production. 4 However, the viscosity of solutions containing 15% or more of CTA is extremely high. Moreover, the used solvent (dichloromethane) is highly volatile.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Therefore, the regulation of the orientation birefringence of optical films has been investigated intensely. 3,4,9,10,14,15 It has been reported that the orientation birefringence (Δn) of a polymer is determined together by the segmental polarizability and the orientation degree (f) 15−17 Here, Δn 0 denotes the intrinsic birefringence of a polymer. n ̅ , ρ, M and N A are the average refractive index, the density, the relative molecular mass, and the Avogadro's constant, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations